Strength Analysis of Metakaolin Based Concrete in Presence of Waste Foundry Sand (International Journal of Innovative Research in Engineering & Management, 2022)
The purpose of this study is to investigate  the results that would be obtained by exchanging cement  for metakaolin and fine aggregate for waste foundry sand.  For the purpose of this inquiry, M-30 grade concrete is  produced, and it is examined for characteristics of hardened  concrete such as compressive strength. Samples with  required dimensions were utilised with Metakaolin at a  constant 10 percent, and the fine aggregate was replaced  with waste foundry sand at weight percentages of 0, 10, 20,  30, and 40 percent. Based on the findings, it appears that  improving the mechanical properties of concrete by mixing  in Metakaolin and waste foundry sand is beneficial. The  best results were obtained by replacing cement and sand  with Metakaolin at a percentage of 10 percent and waste  foundry sand at a percentage of 30 percent, respectively.  The findings indicate that, up to a certain amount of Waste  foundry sand and Metakaolin addition, there is a gain in  mix strength; however, after that point, further addition of  the Metakaolin and Waste foundry sand begins to lower  mix strength. Despite the fact that adding Metakaolin and  waste foundry sand up to a level of ten percent and thirty  percent, respectively, helps in achieving higher strength  than conventional concrete, the inclusion of these materials  is not required. As a result, the use of metakaolin and waste  foundry sand in place of traditional sand aids in the  development of green concrete that is both kind to the  environment and durable.
Keywords: Concrete; Metakaolin; Waste Foundry Sand; Strength; Environment